Habitat characteristics shaping ant species assemblages in a mixed deciduous forest in Eastern India. (30th January 2015) - Parui, Arpan Kumar; Chatterjee, Soumik; Basu, Parthiba
Abstract: Environmental complexity and spatial heterogeneity are important factors influencing the structure of ant species assemblages. This paper documents the effect of different vegetation and environmental factors on ant community structure and functional group composition in different habitat patches. Ants were sampled at 16 sites distributed across five habitat types in the Kuldiha Wildlife Sanctuary. Sampling was performed 10 times over a 2-y period using pitfall traps. A total of 100 species belonging to 41 genera were collected during the study. Ant species richness was best explained by a combination of percentage grass cover, percentage litter cover and number of saplings whereas percentage litter cover and soil nitrogen concentration significantly explained the variation in ant species abundance. Dominant Dolichoderinae were present only at forest edge and were found to be associated positively with percentage bare ground cover and negatively with percentage litter cover. Generalized Myrmicinae, subordinate Camponotini and tropical climate specialists were prevalent in shaded forest habitats whereas opportunists were more common in two types of open habitat. Our study underpins the influence of vegetational complexity, litter and soil chemical properties on the structure and composition of ant species assemblages and various functional groups across forested habitats in this little-studied region.